2012
DOI: 10.1111/j.1750-3841.2012.02897.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Trimethylamine in Spinach, Cabbage, and Lettuce at Alkaline pH by Headspace Solid‐Phase Microextraction

Abstract: Fishy off-flavor in foods is associated with trimethylamine (TMA), which is frequently found in fish and seafood. In this study, TMA was identified for the first time in some leafy vegetables, such as spinach, cabbage, and lettuce, at alkaline pH. The presence of TMA in leafy vegetables under certain circumstances such as high pH and temperature may affect the sensory properties of foods containing these vegetables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The adsorption equilibrium for volatile compounds can be quickly reached due to their low boiling points. Furthermore, analytes show a tendency to desorb at longer adsorption times . Therefore, an adsorption time of 10 min was selected for all extraction needles, and 5 min was selected for the SPME needle.…”
Section: Resultsmentioning
confidence: 99%
“…The adsorption equilibrium for volatile compounds can be quickly reached due to their low boiling points. Furthermore, analytes show a tendency to desorb at longer adsorption times . Therefore, an adsorption time of 10 min was selected for all extraction needles, and 5 min was selected for the SPME needle.…”
Section: Resultsmentioning
confidence: 99%
“…As previously reported, trimethylamine (TMA) was evoking a fishy odor in egg yolk ,, as a result of a high sinapine content in rapeseed meal used for feeding. Shim et al found trimethylamine in spinach, cabbage, and lettuce under alkaline conditions using SPME technique. Latest studies of Jiang et al reported about trimethylamine responsible for the fishy off-flavor in soybean oil and they found a correlation between trimethylamine formation and phosphatidylcholine degradation.…”
Section: Resultsmentioning
confidence: 99%
“…More elaborate instrumental methods have evolved through the years. At present, gas chromatography (Namieśnik et al 2003;Shim and Baek 2012), solidphase micro-extraction (Chan et al 2016;Shim andBaek 2012), or solvent extraction (daCosta et al 1990;Oetjen and Karl 1999), ion mobility (Bota and Harrington 2006;Cheng et al 2017), nuclear magnetic resonance spectroscopy (Podadera et al 2005), ion chromatography (Erupe et al 2010;Li et al 2009), capillary electrophoresis (Li and Lee 2007;Timm and Jørgensen 2002), high-resolution rotational terahertz (THz) spectroscopy (Hindle et al 2018), and high-performance liquid chromatography methods (Cháfer-Pericás et al 2004;Hyötyläinen et al 2001;Romero-González et al 2012) are the most widely adopted techniques to measure the amounts of primary and secondary amines in various matrices. The major advantages of these chromatographic techniques are higher sensitivity, specificity, and ability to determine several substances simultaneously.…”
Section: Introductionmentioning
confidence: 99%